Super-twisting estimation of a virtual output for extremum-seeking output feedback control of bioreactors. (November 2015) - Vargas, A.; Moreno, J.A.; Vande Wouwer, A.
Abstract : Highlights: A virtual output that is a linear combination of reaction rates should be maximized. A bank of super-twisting observers carry out the estimation of the virtual output. A weighted super-twisting observer with constant gains is proposed. A two-level output feedback controller is proposed to maximize the output. The resulting output-feedback controller is tested with simulations of a bioreactor. Abstract: In biotechnological processes such as fed-batch reactors the lack of reliable and robust on-line sensors and the limited number of actuators make the task of operating at optimal conditions very difficult. We present a feedback controller that aims at regulating the substrate concentration at an optimum value such that biomass production is enhanced while by-product formation is not favored. We use a virtual output that is estimated using a bank of weighted super-twisting observers to drive an output-feedback extremum-seeking controller. The only online measurements needed are the biomass concentration and the oxygen and carbon dioxide mass transfer rates. Simulations on a fed-batch bioreactor model show its applicability.